2021
DOI: 10.1111/ipd.12843
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown impact on lifestyle and its association with oral parafunctional habits and bruxism in a Spanish adolescent population

Abstract: Aim To analyse the possible association between decreased physical and social activity and an increase in the use of mobile devices, internet, and social networks with increased anxiety and the appearance of oral parafunctions and bruxism for adolescents before and during COVID‐19. Design A total of 213 adolescents attended private clinics at two different times: before lockdown (T0) and after completion of total lockdown (T1). In T0 and T1, a clinical examination was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
0
21
0
3
Order By: Relevance
“…Fourteen studies85–98 assessed the impact of COVID-19-related lockdown on movement behaviours (physical activity: 10, screen time: 9, sleep duration: 4, and sleep quality: 4) of children with health conditions such as autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), type 1 and type 2 diabetes, obesity, physical disability, neurodevelopmental disability, psychiatric disorder, fragile X-syndrome and dental wear.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies85–98 assessed the impact of COVID-19-related lockdown on movement behaviours (physical activity: 10, screen time: 9, sleep duration: 4, and sleep quality: 4) of children with health conditions such as autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), type 1 and type 2 diabetes, obesity, physical disability, neurodevelopmental disability, psychiatric disorder, fragile X-syndrome and dental wear.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the HPI poll by ADA ( 6 ), the majority of dentists in the United States reported seeing higher numbers of patients with bruxism and TMD. Other studies have shown increased stress levels among the public ( 8 , 13 , 14 ), increased self-reported bruxism ( 15 ), increased prevalence of sleep disorders ( 16 ), and exacerbation of symptoms in TMD patients ( 13 ) following the outbreak of COVID-19. The increase in rate of cracked teeth shown in the present study may be associated with increased stress, bruxism, parafunctional habits and other depressive symptoms that were brought on by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Carrillo-Diaz et al investigate the relationship between a decrease in physical and social activity and an increase in the use of mobile devices, the internet, and social media. There was an increase in anxiety and the appearance of oral para-functions and bruxism for adolescents during COVID-19 pandemic; based on their data, the increase in social network use at night and anxiety levels during lockdown appear to be associated with an increase in self-reported bruxism ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…They also indicated an increase in the outbreak of bruxism after COVID-19 pandemic compared to that before COVID-19 pandemic due to stress originating from the Corona pandemic. Also, they implemented self-reported method to assess bruxism ( 16 ). The controversy between the results of these two studies might be related to race.…”
Section: Discussionmentioning
confidence: 99%